Antibacterial Effect of Ethyl Acetate Fraction of Medicago Sativa on Escherichia coli in Urinary Tract Infections - Ahmed, Alaa Gh.; Al-Atrakji, Mohammed Q.; Al-Wattar, Wifaq M. (Journal of the Faculty of Medicine Baghdad, 2023)
Background:  One of the most dominant bacterial infections is urinary tract infection (UTI), both in the community and the hospital settings Since drug resistance become one of the predominant problems of health worldwide, it is necessary to use new methods to overcome drug-resistant bacteria. In this regard, medicinal plants (Medicago sativa )  are considered one of the richest sources to produce antibiotics.Objectives: evaluate the antibacterial effect of the fraction of ethyl acetate of Medicago Sativa extract against Escherichia Coli isolated from urine samples of patients with urinary tract infections.Methods: throughout this study 85 urine samples were taken from patients attending one of the hospitals in Iraq's Medical City complex, the study was conducted between December 2021 and May 2022, Semi-quantitative culture techniques were used to culture the urine samples, and conventional microbiological methods were used to identify the bacteria. the Kirby-Bauer Disk diffusion method was used for testing antibiotic susceptibility. The antibacterial effect of Medicago Sativa was tested by preparing Medicago sativa crude extract in 85 percent ethanol in the soxhlet apparatus. The extract is then fractionated into ethyl acetate fraction, then the effectiveness against uropathogenic E. coli was tested at various concentrations (25 mg/ml, 50 mg/ml, and 75 mg/ml).Result: 60% of the population was female compared to 40% of the male in UTI patients with E.coli. Concerning age, the majority of study participants (20–39 years) were under 40 years old (56.7%), and all isolates showed complete meropenem sensitivity. The extracts from Medicago Sativa showed significant antibacterial activity against E.Coli.Conclusion: Medicago sativa extracts have excellent potential as an antibacterial agent against uropathogenic E. coli, according to the current investigation findings.